2015
DOI: 10.1177/1470320315610255
|View full text |Cite
|
Sign up to set email alerts
|

Association of the insertion allele of the common ACE gene polymorphism with type 2 diabetes mellitus among Kuwaiti cardiovascular disease patients

Abstract: Background and objectives:The D allele of the common angiotensin-converting enzyme (ACE) I/D gene polymorphism (rs4646994) predisposes to type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). However, results on which allele predisposes to disease susceptibility remain controversial in Asian populations. This study was performed to evaluate the association of the common ACE I/D gene polymorphism with both T2DM and CVD susceptibility in an Arab population. Methods: We genotyped the ACE I/D polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…This inference was also supported by several genetic based studies which showed that the carriers of ACE II genotype are at increased risk of developing insulin resistance [32,33] than ACE DD genotype carriers [32,34]. The ACE II genotype dependent risk of diabetes was also supported by the findings of current study and the report of Al-Serri et al also showed that ACE II genotype increase the risk of diabetes in CVD patients [12].…”
Section: Ace I/d Polymorphism Associated Disease Risksupporting
confidence: 85%
See 2 more Smart Citations
“…This inference was also supported by several genetic based studies which showed that the carriers of ACE II genotype are at increased risk of developing insulin resistance [32,33] than ACE DD genotype carriers [32,34]. The ACE II genotype dependent risk of diabetes was also supported by the findings of current study and the report of Al-Serri et al also showed that ACE II genotype increase the risk of diabetes in CVD patients [12].…”
Section: Ace I/d Polymorphism Associated Disease Risksupporting
confidence: 85%
“…Likewise, D allele was also reported to be strongly associated with diabetes in Saudi Arabian and Indian Punjabi populations [25,26]. Conversely, Kuwaiti and North Indian population-based studies supported I allele or II genotype as risk factor for diabetes [12,27] which also favor findings of the current study. Overall, several studies have concluded that ACE I/D polymorphism is associated with diabetes; however, the risk genotype is variable in different populations and has to be elucidated for its association with disease for the target population or ethnic group.…”
Section: Association Of Clinical Anthropometric and Biochemical Parasupporting
confidence: 56%
See 1 more Smart Citation
“…Also, the DD genotype distribution was found to be significantly higher in diabetic patients in Tunis [ 6 , 35 ] and in Bahrain [ 36 ]. The ACE I allele was found to be associated with diabetes among Kuwaitis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association of advanced age, sex, nutrition, smoking, metabolic syndrome, and physical inactivity has been studied extensively and documented in the Kuwaiti population [ 2 , 6 , 7 ]. Limited studies have focused on the association of genetic factors with CHD in either the Kuwaiti population [ 8 10 ] or among Arab ethnic groups in general [ 11 ].…”
Section: Introductionmentioning
confidence: 99%